The Effects Of Online Customer Reviews And Customer Experiences On Reuse Intention Of Mobile Food Ordering Application (MFOA) - Kristyanto Djoko Purnomo; Awan Kostrad Diharto (Relevance: Journal of Management and Business, 2021)
This research was conducted in response to the research gap between some previous research by Auliya (2019), which stated that online customer reviews did not have significant effects on the reuse intention. Meanwhile, Alalwan (2020) in Hariguna & Ruangkanjanases (2020) found different results; namely, online customer reviews had a significant effect on the reuse intention. Therefore, this research objective was to determine the effects of online customer reviews and customer experiences on reuse intention through satisfaction. The research population consisted of Mobile Food Ordering Application (MFOA) users in Central Java with a total sample of 251 respondents. This research used a random sampling technique. Furthermore, the data analysis of this research used the Smart PLS 3.0 application. The research results reported that online customer reviews had a significant positive effect on satisfaction. Besides, online customer reviews, customer experience, and satisfaction had significant effects on reuse intention. There were two points related to the indirect relationship in this research; namely, both online customer review and customer experience had significant effects on reuse intention through satisfaction.